Struktur Komunitas Bulu Babi (Echinoidea) di Perairan Pantai Gunung Payung, Bali - Pramesti, Addiani Tannia; Giri Putra, I Nyoman; Pratama Atmaja, Putu Satya (Journal of Marine Research and Technology, 2025)
Echinoidea are benthos animals that play an important role in aquatic ecosystems. Generally, Echinoidea live in association with benthic communities such as seagrasses, macroalgae, and coral reefs. The benthic community is an organism living on the seabed that plays a role in the food chain for aquatic organisms. This study aimed to determine the structure of the Echinoidea community and the correlation of Echinoidea density with benthic community cover on Gunung Payung Beach, Bali. Echinoidea sampling method using Benthos Belt Transect (BBT) with a length of 70 meters perpendicular to the sea and a width of 1 meter each to the right and left. The benthic community was observed using the Line Intercept Transect (LIT) method. Echinoidea was found to total 531 individuals from 4 families and 6 species. Echinoidea, which has the highest density, is Echinometra mathaei at 1 ind/m 2 . The diversity index ranges from 0.27-1.71, low to medium category. The diversity index ranges from 0.39-0.95, low to high category. The dominance index ranged from 0.19 - 0.86, low to high category. The most dominant benthic community cover was found to be Dead Coral (DA), Dead Coral Algae (DCA), Macroalgae (MA), and Seagrass (SG). Pearson correlation analysis results between the percentage of benthic community cover and Echinoidea density has a positive direction, namely DA, DCA, Coral Massive, rubble, and Sand worth 0.364-0.989, which has a low to very high category. The negative direction correlation is MA and SG of -0.470 and -0.857 sufficient and very high categories.